Neuronal Cell Culture Methods and Protocols - Amini, Shohreh.; Amini, Shohreh.; White, Martyn K.; White, Martyn K. (Methods in Molecular Biology, 2013)
In Neuronal Cell Culture: Methods and Protocols, the latest aspects of the culture of neural cells are explored by experts in the field who also explain the practical and theoretical considerations of the techniques involved.  Starting with a general overview of the neuronal culturing principles that are described, this detailed volume covers cell line models for neural cells, the isolation and propagation of primary cultures, stem cells, transfection and transduction of neural cultures, and other more advanced techniques.  Written for the Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Practical and easy to use, Neuronal Cell Culture: Methods and Protocols will be of interest to scientists at all levels developing cell culture models for neuroscientific studies.